GAMBARAN PENGALAMAN PERAWAT TENTANG BANTUAN HIDUP DASAR (BHD) DI RUANG INTENSIVECARE UNIT (ICU) RUMAHSAKIT SANTA ELISABETH MEDAN TAHUN 2023 - Rusmauli; Tiodor Simarmata (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Work experience is the length of time employees work at work from the time they are accepted into the workplace until now. Basic life support (BHD) is an effort made to maintain life when the victim experiences respiratory arrest and cardiac arrest. The purpose of the study is to determine the Nurse’s Experience on Basic Life Support (BHD) in the Intensive Care Unit (ICU) Room of Santa Elisabeth Hospital Medan 2023. This study used qualitative methods where the data collection is carried out with interviews as many as 4 questions so as to be able to dig deeper into nurses’ experiences about basic life support. The sampling technique uses purposive sampling as many as 5 participants. The data analysis technique used is thematic analysis.The results of the study are obtained: The nurse’s experience of basic life support is to maintain breathing so that respiratory arrest and cardiac arrest do not occur, Basic life support is an interesting experience because in BHD requires high energy / concentration and adds insight for nurses to do BHD, Basic life support can increase cohesiveness and teamwork and doctors on duty in doing BHD, Basic life support is understanding and skills because nurses have done BHD training, basic life support can be provided to patients who experience respiratory arrest and cardiac arrest. The results In this study, the experience of nurses on basic life support is supported by updated BHD knowledge and training to add to the experience that nurses have followed.